Biochemical alterations in native and exotic oyster species in Brazil in response to increasing temperature - Moreira, Anthony; Figueira, Etelvina; Pecora, Iracy L. [UNESP]; Soares, Amadeu M. V. M.; Freitas, Rosa (Elsevier B.V., 2017)
The increase of temperature in-marine coastal ecosystems due to atmospheric greenhouse gas emissions is becoming an increasing threat for biodiversity worldwide, and may affect organisms' biochemical performance, often resulting in biogeographical shifts of species distribution. At the same time, the introduction of nonnative species into aquatic systems also threatens biodiversity and ecosystem functions. Oysters are among the most valuable socio economic group of bivalve species in global fishery landings, and also provide numerous ecosystem services. However, the introduction of non-native oyster species, namely Crassostrea gigas for aquaculture purposes may threaten native oyster species, mainly by out competing their native congeners. It is therefore of upmost importance to understand physiological and biochemical responses of native and introduced oyster species in a scenario of global temperature rise, in order to provide knowledge that may allow for better species management. Hence, we compared biochemical alterations of the introduced C gigas and the native Crassostrea brasiliana, the most important oyster species in Brazil, in response to different thermal regimes for 28 days (24, 28 and 32 C). For this, metabolism (ETS), energy content (GLY), antioxidant system (SOD, CAT and GSH/GSSG) and cellular damage (LPO) were assessed in adult and juvenile specimens of both species. Juvenile C gigas were the most affected by increased temperatures, presenting higher mortality, more pronounced antioxidant response (SOD), whereas adults were more tolerant than juveniles, showing no mortality, no significant changes in antioxidant enzymes activity neither energy expenditure. Native C. brasiliana juveniles presented lower mortality and less pronounced biochemical alterations were noted at higher temperature comparing to non-native C. gigas juveniles. Adult C brasiliana were the least responsive to tested temperatures. Results obtained in this study bring interesting new insights on different oyster species life stages' physiological and biochemical tolerance towards thermal stress. The native species C. brasiliana showed ability to maintain biochemical performance at higher temperatures, with less pronounced biochemical changes than the non-native species. The introduced (C. gigas) showed to be more sensitive, presenting biochemical alterations to cope with the increase of temperature. Despite the lower observed fitness of the introduced species to temperatures closer to those naturally experienced by the native species, the ability of C gigas to cope with higher temperatures should still raise concerns towards the native species C. brasiliana management and protection. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: Crassostrea brasiliana; Crassostrea gigas; Temperature; Oxidative stress; Metabolism; Native; Introduced